A educação informal e o rap como agente educativo - Alexandre Felipe Fiuza; Iolanda Macedo (EccoS – Revista Científica)
In this text are broached the relationship between rap music and the educational processes. To achieve this goal, the study deals with the conceptualization of the modalities of education, namely formal, non-formal and informal education, based on national and foreign bibliography. Considering the object of study, this paper is based on interdisciplinary reflections, consisting of theoretical and methodological approaches from the fields of Education, Music, Communication and Sociology of Culture. These theoretical frameworks contribute to the accuracy of concepts and the observation of the multiple dimensions that hip hop, and specifically rap, holds as a social and cultural phenomenon. By focusing on the particularity of informal education, which is even more prevalent in the so-called knowledge or media society, this study aims to contribute to the discussion of educational processes intrinsic to the culture industry and the media, and their significant influence on the audience.